Youth working in tobacco farming: effects on smoking behavior and association with health status - Ethel Alderete; Jennifer Livaudais-Toman; Celia Kaplan; Steven E. Gregorich; Raúl Mejía; Eliseo J. Pérez-Stable (BMC, 2020)
Abstract Background Cultivation of tobacco raises concerns about detrimental health and social consequences for youth, but tobacco producing countries only highlight economic benefits. We compared sociodemographic and health-related characteristics of school-age youth who worked and did not work in tobacco farming and assessed the effects on smoking behavior and health at 1 year. Methods We used existing data collected in the province of Jujuy, Argentina where 3188 youth 13 to 17 years of age from a random middle school sample responded to longitudinal questionnaires in 2005 and 2006. Multivariate logistic regression models predicted association of tobacco farming work with health status and smoking behavior at 1 year. Results 22.8% of youth in the tobacco growing areas of the province were involved in tobacco farming. The mean age of initiation to tobacco farming was 12.6 years. Youth working in farming had higher rates of fair or poor versus good or excellent self-perceived health (30.3% vs. 19.0%), having a serious injury (48.5% vs. 38.5%), being injured accidentally by someone else (7.5% vs. 4.6%), being assaulted (5.5% vs. 2.6%), and being poisoned by exposure to chemicals (2.5% vs. 0.7%). Youth working in tobacco farming also had higher prevalence of ever (67.9% vs. 55.2%), current (48.0% vs. 32.6%) and established smoking (17.8% vs. 9.9%). In multivariate logistic regression models tobacco farming in 2005 was associated with significant increased reporting of serious injury (OR = 1.4; 95%CI 1.1-2.0), accidental injury by someone else (OR = 1.5; 95% 1.0-2.1), assault (OR = 2.2; 95% CI 1.3-3.8), and poisoning by exposure to chemicals (OR = 2.5; 95% CI 1.2-5.4). Tobacco farming in 2005 predicted established smoking 1 year later (OR = 1.5; 95% CI 1.1-2.0). Conclusion Youth who work in tobacco faming face a challenging burden of adversities that increase their vulnerability. Risk assessments should guide public policies to protect underage youth working in tobacco farming. (298 words).